2004
DOI: 10.1111/j.1365-2257.2004.00643.x
|View full text |Cite
|
Sign up to set email alerts
|

The use of vinca alkaloids in adult patients with refractory chronic idiopathic thrombocytopenia

Abstract: The aim of the study was to evaluate the application of vincristin or vinblastin in patients with chronic idiopathic thrombocytopenic purpura (ITP), resistant to corticosteroids or with partial contraindication to their application. Twenty-two patients were treated with vincristin or vinblastin in doses of 2 and 10 mg, respectively. Eight of these patients were additionally administered prednisone in an oral dose of 0.5 mg/kg body mass (bm). Two-hour intravenous infusions of drugs were made once a week, at lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 12 publications
1
20
0
Order By: Relevance
“…Thus, rituximab would be preferred over splenectomy [9]. Vinca alkaloids have also been used as a second-line therapy in steroid-resistant ITP, with moderate success [11].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, rituximab would be preferred over splenectomy [9]. Vinca alkaloids have also been used as a second-line therapy in steroid-resistant ITP, with moderate success [11].…”
Section: Discussionmentioning
confidence: 99%
“…Studies that included more than 10 patients are reported in Table 3 [62][63][64][65][66]. The efficacy of vinca-alkaloids seems to be higher in newly diagnosed ITP than in persistent and chronic ITP.…”
Section: Vinca-alkaloids: Vincristine Vinblastinementioning
confidence: 97%
“…Many approaches exist, and because all have some efficacy, treatments tend to be physician- or center specific. Choices for severe and refractory disease include combination strategies [2], rituximab [3,4], splenectomy [5,6], vincristine [2,7], azathioprine/6MP [8-13], mycophenylate mofetil [14,15], danazol [16,17], and in severe cases, cyclophosphamide [18]. Few comparative studies exist to determine a “best next-line” therapy for these patients [19].…”
Section: Introductionmentioning
confidence: 99%